The temporal requirement of IL-4Rα signalling in allergic asthma and the role of IL-4Rα-responsive Regulatory T cells in restraining allergic airway inflammation - Khumalo, Jermaine (Department of Pathology, 2020)
Allergic asthma is a chronic inflammatory airway disease driven predominantly by a TH2 immune response to environmental allergens. The asthma pathology is predominantly elicited by IL-4 and IL-13 signalling via IL-4Rα-signalling which is essential for driving TH2-type immunity to allergens. Interestingly, the failure by regulatory T cells to maintain tolerance during allergic asthma, suggested to be driven by TH2 inflammatory signals, still remains elusive and anti-TH2 therapies with the potential to effectively reduce airway obstruction and inflammation in allergic asthma, have had limited success. Therefore, we aimed to investigate the function of IL-4/IL-13 responsive regulatory T cells in a TH2 rich environment and the temporal requirement of IL-4Rα-signalling in asymptomatic and acute airway disease. Objective 1: We investigated potential therapeutic effects of selective inhibition of this pathway in mice with established allergic airway disease and systemically sensitised mice to prevent the onset of the disease. We used RosacreERT2IL-4Rα-/lox mice, a novel, tamoxifen inducible IL-4Rα knockdown model to investigate the role of IL-4/IL-13 signalling during the effector phase of ovalbumin induced allergic airway disease (AAD) and for the onset of the disease. The deletion of the IL-4Rα had a therapeutic effect on established AAD and prevented the development of ovalbumin induced airway hyperreactivity, goblet cell metaplasia and eosinophilia in allergensensitised mice. We concluded that the abrogation of IL-4Rα signalling after allergic sensitisation would have significant therapeutic benefit for TH2 type allergic asthma. Objective 2: The canonical IL-4Rα-signalling, was investigated on its role on Foxp3+ Tregs in allergic asthma with aims to re-establish tolerance during allergic asthma. We used transgenic Foxp3cre IL-4Rα-/lox mice IL-4Rα-/lox mice to investigate the role of IL-4/IL-13 signalling during the induction or maintenance of tolerance in house dust mite-induced ADD. The depletion of IL-4Ra on Foxp3+ Tregs exacerbated airway hyperreactivity and airway inflammation in allergen- sensitised mice. Interestingly, a reduced induction of Foxp3+ Tregs in peripheral tissue and an accompanying increased IL-33 induced ILC2 driven inflammation in the lung responsible for the exacerbation of TH2 acute disease. Conclusively, the IL-4Rα responsive Foxp3+ T regulatory cells are key in maintaining tolerance in type 2 innate immune driven allergic asthma, therefore the TH2 environment has both an innate immune specific regulative role in local lung tissue and induction of Foxp3+ Tregs in peripheral tissue during AAD. A combined targeting of the pathogenic TH2 environment in anti-TH2 therapy and the augmentation of regulatory T cell function in the local lung tissue is necessary to inhibit both adaptive and innate drivers of TH2 inflammation in allergic disease.